2018
DOI: 10.1007/s12298-018-0559-7
|View full text |Cite
|
Sign up to set email alerts
|

Calcium alginate encapsulated synthetic seed production in Plumbago rosea L. for germplasm exchange and distribution

Abstract: L. (Plumbaginaceae), is a medicinal shrub commercially exploited for its naphthoquinone principle, plumbagin, extracted from the roots especially for treating skin disorders. As the plant is exploited from the wild without being replenished, conservation of the species becomes inevitable. Synthetic seeds would provide for effective conservation, germplasm exchange and distribution of this species. A reliable protocol for synthetic seed production in has been developed encapsulating the axillary buds. The axill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
1
10
0
1
Order By: Relevance
“…Artificial seeds are encapsulated tissue culture resultant micropropagules that hold plant conversion potential and is employed for conservation, germplasm exchange and distribution. The use of nodal segments as explant for syn seed production abolishes the fortuitous of somaclonal variation [51]. Artificial seed production using nodal segments in Tinospora cordifolia, a medicinal plant becoming extinct owing to high commercial exploitation is not yet reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Artificial seeds are encapsulated tissue culture resultant micropropagules that hold plant conversion potential and is employed for conservation, germplasm exchange and distribution. The use of nodal segments as explant for syn seed production abolishes the fortuitous of somaclonal variation [51]. Artificial seed production using nodal segments in Tinospora cordifolia, a medicinal plant becoming extinct owing to high commercial exploitation is not yet reported.…”
Section: Resultsmentioning
confidence: 99%
“…The artificial seeds are bounded by a defensive coating, which delivers essential protection throughout storage, handling and transportation. The coating could integrate plant nutrients or plant growth regulators that aid its conversion into plantlet [51]. In the investigation, nodal segments from the in vitro cultures were encapsulated using sodium alginate (1, 2 2.5 and 3 5% m/v) in modified MS medium and calcium chloride (50, 75 and 100 200 mM).…”
Section: Synthetic Seed Formationmentioning
confidence: 99%
“…In the presence of 1.5 mg/L BAP and 0.3 mg/L NAA nodal explants gave 80% shooting response with highest number of shoots per explant (13.62 ± 0.8) [30]. Nodal explants cultured on MS medium supplemented with 1.5 mg/L BA and 1.0 mg/L IAA have given earliest bud initiation (7.94 ± 0.22 days), maximum shoot length (5.33 ± 0.19 cm) and Maximum shoot proliferation (5.28 ± 0.26 shoots) [31]. Shoot induction was also done by using leaf explants.…”
Section: Tissue Culture Of P Indicamentioning
confidence: 99%
“…On the other hand, lower concentrations of sodium alginate (1 or 2%) or calcium chloride (25 or 50 mM) produced weak structures with no define shape which disintegrated while being handled [45,60]. In general, it is concluded that 2-3% sodium alginate gel exposed for 30 min to 100 mM calcium chloride is an optimal combination for acceptable bead production and subsequent satisfactory germination response [29,30,61]. In the present study, the combination of 2.5% sodium alginate with 100 mM of calcium chloride for a 30 min complexation time resulted in the formation of high quality beads, easy to handle (hardness 0.27 ± 0.02 N), followed by an unimpeded germination response.…”
Section: Encapsulation and Artificial Seed Germination Assessmentmentioning
confidence: 99%